Diversity structure of the Schumpeterian evolution: An axiomatic approach - Andrzej Malawski; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2006)
The purpose of the paper is to impose the diversity structure on the Schumpeterian evolution modelled axiomatically within a dynamical system approach to the Arrow-Debreu theory of general equilibrium. In this framework two basic forms of economic life studied by Schumpeter, i.e., the circular flow and economic development are investigated as specific properties of a dynamic system, where single production systems being the parts of the Debreu models change in the definite environment according to the rules of the Schumpeterian evolution. Moreover, the Sterling diversity-triplet concept based on subcategories of variety, balance and disparity, is slightly modified and applied to serve as a tool for rigorous analysis of innovative and cumulative changes in production system with respect to diversity structure. Finally, integrating diversity aspects into a dynamic system approach, the study identifies innovative processes as the source of growing diversity in the Schumpeterian vision of economic development.
Keywords: D50; O30; 330; diversity; Schumpeterian evolution; Arrow-Debreu theory; dynamic system approach